Menguji Transparansi dan Partisipasi Publik dalam Politik Legislasi: Refleksi atas Prolegnas dan Prolegda di Indonesia - Putri, Mutiara; Ananda, Reza; Puja Kusuma, Erika; Dwi Cahyono, Leo (Adagium: Jurnal Ilmiah Hukum, 2025)
This article discusses the structural and normative obstacles to realizing meaningful public participation in the preparation of legislative programs. The National Legislation Program (Prolegnas) and Regional Legislation Program (Prolegda) serve as the primary instruments for planning statutory law making in Indonesia. Ideally, both programs should be formulated in a participatory and transparent manner to align with the needs of the public. However, in practice, the legislative planning process remains elitist and opaque, resulting in a disconnect between the enacted legal products and public aspirations. This study employs a library research method with a normative-juridical and critical-theoretical approach to examine the extent to which public participation and transparency are accommodated in the drafting of legislative programs, as well as to identify existing barriers. The findings indicate that public involvement remains symbolic and insufficiently institutionalized within the legislative system. Structural obstacles such as elite domination and normative limitations, including the lack of detailed regulations on public participation mechanisms, are identified as major factors. This study recommends strengthening participatory mechanisms and information transparency at every stage of Prolegnas and Prolegda formulation as part of a broader legal-political reform rooted in deliberative democracy.